The investment performance for the scheme of Amanah Saham Nasional (ASN) for the year 2005 to 2009: the case for Permodalan Nasional Berhad (PNB) / Suzana Ab Rahman - Ab Rahman, Suzana (2010)
This project paper studies about measurement the performances of fund for product in ASNB towards benchmark provide from KLCI based on the industry. The aim is to increase the total return and average total return of the fund more than benchmark guideline. By studying this case, I clarify the achievement for the product. Besides, the asset allocation for every three year back. The studies include the timely total return for the period from 2005 until 2009 that is categorized into ASN product. In this case, also provide what are other elements contribute in performances of fund for the ASN scheme and in what ways the management especially PNB manage the risk and come out with the new idea. Data have been collected from archives, interviews, online newspapers and published reports. These studies have found out that economic condition, the preparation with management risk, and others factor. As conclusion, the researcher have been seen the gap identification between five years above. Master prospectors PNB June 30, 2010 shown the annual total return for ASN on 2008 it worst proven by negatively percentage and not be able to achieve benchmark of the industry. But in year 2009, the percentage have been increase with positive percentage and over the benchmark of industry. From this study found that, factors acquisition of equities, increase in value of equities as the stock market performances positively and level of return on equities investment will contributes the movement performance of fund ASN scheme.